2012
DOI: 10.1108/00907321211228291
|View full text |Cite
|
Sign up to set email alerts
|

User perceptions of ebooks versus print books for class reserves in an academic library

Abstract: PurposeThe purpose of this paper is to present the results of a pilot program at Dickinson College where select reserve books for a class were purchased as ebooks and linked through the course management system. The paper aims to shares the results of survey data, a focus group session, and usage statistics to evaluate the pilot.Design/methodology/approachThe study uses mixed methods with survey, focus group, and usage analysis.FindingsThe study found a much higher use of ebooks over print reserves. The survey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 10 publications
1
13
0
4
Order By: Relevance
“…Column B and eBook Sig shows the range of 5.573 points which means that if students use eBooks, their learning outcomes will be higher by 5.573 points compared to those using printed books. It can be concluded that the use of eBooks in rural schools is able to further improve students' learning outcomes compared to the use of printed book s. Some of the studies that support these findings are those of Lai (2016), Liaw & Huang (2014), Chen (2013), Bradshaw (2005), Goodwin (2014), Woo (2011), Massis (2010, Bronshteyn (2007), deNoyelles & Seilhamer (2013), Tucker (2012), Letchumanan & Muniandy (2016), Rojeski (2012), and Parkes (2007). The results that contradict these findings explain that the printed book is still relevant (Jeong, 2012;Katsarska, 2005;Lewellen, Bischof, & Plum, 2016;Nwagwu & Okafor, 2014;Darsono, Wi narno, & Slamet, 2018).…”
Section: Result Discussion and Suggestionsmentioning
confidence: 95%
“…Column B and eBook Sig shows the range of 5.573 points which means that if students use eBooks, their learning outcomes will be higher by 5.573 points compared to those using printed books. It can be concluded that the use of eBooks in rural schools is able to further improve students' learning outcomes compared to the use of printed book s. Some of the studies that support these findings are those of Lai (2016), Liaw & Huang (2014), Chen (2013), Bradshaw (2005), Goodwin (2014), Woo (2011), Massis (2010, Bronshteyn (2007), deNoyelles & Seilhamer (2013), Tucker (2012), Letchumanan & Muniandy (2016), Rojeski (2012), and Parkes (2007). The results that contradict these findings explain that the printed book is still relevant (Jeong, 2012;Katsarska, 2005;Lewellen, Bischof, & Plum, 2016;Nwagwu & Okafor, 2014;Darsono, Wi narno, & Slamet, 2018).…”
Section: Result Discussion and Suggestionsmentioning
confidence: 95%
“…The definitions of these aspects tend to be elusive, and often overlap. A brief review of the LIS literature seems to suggest that definitions of user experience tend to emphasize products and systems (Gallant & Wright, 2014;Majors, 2012;Norman & Nielsen, n.d.;Yue & Beisler, 2014;) while user perception definitions mainly address services (Lupien, 2007;Ouellete, 2011;Rehman, Shafique, & Mahmood, 2011;Rojeski, 2012). With a specific focus on language and how it impacts information searching online, the current study employed a web survey to gather information on bi/multilingual users' experience and perceptions on searching for information on the Internet and on electronic databases.…”
Section: Introductionmentioning
confidence: 98%
“…Some purport there is a preference toward print over electronic textbooks (Westfall, 2011), and that electronic versions of books are used only for "obtaining snippets of information and fact finding" rather than actual reading (Nicholas et al, 2010, p. 278). Others say that electronic versions of texts are used more in reserves compared to print versions (Rojeski, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%